The effectiveness of minibus taxis as an alternative out of home advertising medium - AT Roux (The Retail and Marketing Review, 2015)
The evolution of transit advertising offers marketers a whole range of new opportunities to engage and reinforce their advertising messages, and even to entertain commuters. Minibus taxis are the most-viewed Out-of-home advertising medium, and the dominant mode of transport in South Africa. Despite the potential opportunities and the reach of minibus taxi advertising in the country, there is a lack of understanding of the effectiveness of this medium from an emerging perspective. Therefore, this study attempts to fill this lacuna by investigating the relationships between constructs that might further contribute to the effectiveness of minibus taxi advertising. The target audience comprises regular minibus taxi commuters at six of the largest taxi ranks in Tshwane. Judgement sampling was used; and a total of 1200 questionnaires were completed. The results show that the strengths of the relationships differ: the strongest relationship was found between commuters’ view of minibus taxi advertising and the effectiveness of minibus taxi advertising; while the weakest relationship was between the attitude towards advertising in general, and the perceptions of minibus taxi advertising. The research is beneficial to marketers who intend to make use of this conduit, in order to target minibus taxi commuters – who are typically the key decision-makers in household purchases.